2000
DOI: 10.15760/etd.1044
|View full text |Cite
|
Sign up to set email alerts
|

Academic Advising Structures that Support First-year Student Success and Retention

Abstract: Academic advising has been touted as a key to student success and retention.Today's academic advising delivery models vary considerably and little is known about the efficiency and effectiveness of these models. The purpose of this study was to determine if there is a relationship between how academic advising is delivered to firstyear students at a four-year public, high research activity university located on the west coast and the students' satisfaction with advising, advising learning outcomes, and retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…McFarlane (2013) investigates the responses of 628 first-year students in their attitudes and experience with advising. Results showed that student retention and major change is related to who advises them.…”
Section: Discussionmentioning
confidence: 99%
“…McFarlane (2013) investigates the responses of 628 first-year students in their attitudes and experience with advising. Results showed that student retention and major change is related to who advises them.…”
Section: Discussionmentioning
confidence: 99%